Online Hating as Modern Manifestation of Nietzschean Ressentiment. - Sinelnikova, Maria (Problems / Problemos, 2022)
The article analyses the modern phenomenon of hating in the light of the Nietzschean concept "ressentiment". It is concluded, that hating can be considered as a kind of the ressentiment experience. This confirms the legitimacy of the "hating ressentiment" concept introduction, which identifies a hater as a person of ressentiment. Hater uses his destructive potential to harass online and persecute everyone whose position or opinion he/she does not share. When all the resources of unfounded criticism of the hater are exhausted, he/she resorts to ressentiment, online. Due to this, ressentiment acquires a new form of expression, namely, hating ressentiment, which is defined as a radical and acute form of ressentiment, corresponding to the form of hatred with which a hater treats everyone in whose place he/she would like to be.